The Use Of Swearing Expression In A Scottish Movie Entitled Sweet Sixteen (A Sociopragmatics Study) - Uzlifatus Saadah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
This article examines the types of swearing employed by the characters in the movie Sweet Sixteen, knowing how the contextual situation affects the use and the meaning of swearing, and knowing how the sociocultural background of the characters influences the level of swearing' offensiveness. This research is a descriptive qualitative research under the framework of Sociopragmatics study. The relationship between social phenomena and methods becomes the focus of this research.